The sum of 3 numbers, the sum of their squares, and the sum of their cubes are all equal to 6.
Find the product of these 3 numbers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A solution which resembles the problem title! Nice solution with the right identities used at the right place. Thanks for the solution
did the same way!!
Where did the -3abc come from?
Or you can use Newton's Sum which is very systematic and much more easy to use to construct a polynomial with a,b,c as roots. After that divide the constant term by -1 to get the answer.
Can one solve for the value of the 3 numbers? I presume they must be complex
Log in to reply
They are complex and yes the problem is not worth to solve for a,b,c
Letting a , b , c be the numbers, one has
3 6 = 6 2 = ( a + b + c ) 2 = a 2 + b 2 + c 2 + 2 a b + 2 b c + 2 a c = 6 + 2 a b + 2 b c + 2 a c .
Thus a b + b c + a c = 1 5 . Let P = a b c .
The polynomial
( x − a ) ( x − b ) ( x − c ) = x 3 − ( a + b + c ) x 2 + ( a b + b c + a c ) x − a b c = x 3 − 6 x 2 + 1 5 x − P .
Since this polynomial equals zero when x = a , b , c , one has
a 3 − 6 a 2 + 1 5 a − P = 0
b 3 − 6 b 2 + 1 5 b − P = 0
c 3 − 6 c 2 + 1 5 c − P = 0 ,
and adding these equations gives
( a 3 + b 3 + c 3 ) − 6 ( a 2 + b 2 + c 2 ) + 1 5 ( a + b + c ) − 3 P = 0
6 − 3 6 + 9 0 − 3 P = 0 ,
whence P = 2 0 .
It can simply be shown that: (a+b+c)^3+2 (a^3+b^3+c^3)-3 (a^2+b^2+c^2)(a+b+c)=6abc Since, (a+b+c), (a^3+b^3+c^3), (a^2+b^2+c^2) = 6 Then all terms on the left hand side within the brackets can be computed easily. Then after dividing through by 6 on both sides and computing the left hand side your left with 20=abc
Problem Loading...
Note Loading...
Set Loading...
Let a,b,c are three such numbers then, we are given a + b + c = 6 , a 2 + b 2 + c 2 = 6 , a 3 + b 3 + c 3 = 6 .
( a + b + c ) 2 = 3 6 ⇒ a 2 + b 2 + c 2 + 2 a b + 2 b c + 2 c a = 3 6 ⇒ 6 + 2 ( a b + b c + c a ) = 3 6
⇒ a b + b c + c a = 1 5 .....(1)
Now, a 3 + b 3 + c 3 − 3 a b c = ( a + b + c ) ( a 2 + b 2 + c 2 − a b − b c − c a ) .
⇒ 6 − 3 a b c = 6 × ( 6 − 1 5 ) . [ f r o m ( 1 ) ]
⇒ 3 a b c = 6 0 ⇒ a b c = 2 0